2019
DOI: 10.1039/c9sc01347d
|View full text |Cite
|
Sign up to set email alerts
|

Generalizing metallocene mechanochemistry to ruthenocene mechanophores

Abstract: This work establishes ruthenocene as new metallocene-based mechanophores that exhibit an intriguing combination of force-free thermal stability and mechanical lability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 54 publications
0
47
0
3
Order By: Relevance
“…Metallocenes play a pivotal role in the development of organometallic chemistry. The most studied members of the family are metallocenes of the transition metals, the reactivity and properties of which are remarkably diverse, leading to widespread applications in established areas such as olefin polymerization catalysis [1] and polymer chemistry, [2,3] whilst also accounting for new developments in small-molecule activation [4,5] and redox-active materials. [6,7] Metallocenes are also prominent in f-element chemistry owing to their distinct catalytic and stoichiometric reactivity, [8,9] and for their ability to provide platforms for the study of fundamental aspects of chemical bonding in lanthanide and actinide compounds.…”
Section: Isolation Of a Perfectly Linear Uranium(ii) Metallocenementioning
confidence: 99%
“…Metallocenes play a pivotal role in the development of organometallic chemistry. The most studied members of the family are metallocenes of the transition metals, the reactivity and properties of which are remarkably diverse, leading to widespread applications in established areas such as olefin polymerization catalysis [1] and polymer chemistry, [2,3] whilst also accounting for new developments in small-molecule activation [4,5] and redox-active materials. [6,7] Metallocenes are also prominent in f-element chemistry owing to their distinct catalytic and stoichiometric reactivity, [8,9] and for their ability to provide platforms for the study of fundamental aspects of chemical bonding in lanthanide and actinide compounds.…”
Section: Isolation Of a Perfectly Linear Uranium(ii) Metallocenementioning
confidence: 99%
“…Mechanistic studies have revealed that the use of F value accounts for variations in temperature, solvent, concentration, sonication amplitude, etc., but that the initial contour length (M n ) of the polymer does matter, with shorter polymers having higher F values (e.g., for a polybutadiene based gDCC polymer, F ¼ 0.92 for M n ¼ 59 kDa vs. F ¼ 0.69 for M n ¼ 92 kDa). 35 This quantication strategy has been applied to studies of the relationship between covalent bond strength and mechanical strength, 38,39 the mechanochemistry of metallocenes 40,41 the chain dynamics of cyclic polymers 42 under high strain rate elongational ows, and the subtle inuence of stereochemical effects on the mechanical reactivity of Diels-Alder adducts. 37…”
Section: Introductionmentioning
confidence: 99%
“…In order to characterize the mechanochemical reactivity of the coumarin dimer, we targeted multi-mechanophore polymer P1 (Table 1), which uses a non-scissile gDCC mechanophore as an internal standard to characterize the relative strength of a scissile mechanophore co-repeating unit. [33][34][35] Briefly, a coumarin dimer macrocycle was synthesized via ring closing metathesis (RCM). The stereochemistry and regiochemistry of the coumarin dimer in the macrocycle (syn and head-to-tail, respectively) are enforced by the Z alkene tether, which restricts the arrangement of the two coumarin moieties for [2+2] photodimerization ( Figure 1b).…”
mentioning
confidence: 99%